Quantification of cysteine hydropersulfide with a ratiometric near-infrared fluorescent probe based on selenium–sulfur exchange reaction - Han, X; Yu, F; Song, X; Chen, L (Royal Society of Chemistry, 2016)
Cysteine hydropersulfide (Cys-SSH) plays primary roles in the synthesis of sulfur-containing cofactors, regulation of cellular signaling, activation or inactivation of enzyme activities, and modulation of cellular redox milieu. However, its biofunctions need to be further addressed due to the fact that many issues remain to be clarified. Herein, we conceive a novel ratiometric near-infrared fluorescent probe Cy-Dise for the sensitive and selective detection of Cys-SSH in living cells and in vivo for the first time. Cy-Dise is composed of three moieties: bis(2-hydroxyethyl) diselenide, heptamethine cyanine, and D-galactose. Cy-Dise exhibits a satisfactory linear ratio response to Cys-SSH via a selenium–sulfur exchange reaction in the range of 0–12 μM Cys-SSH. The experimental detection limit is determined to be 0.12 μM. The results of ratio imaging analyses confirm the qualitative and quantitative detection capabilities of Cy-Dise in HepG2 cells, HL-7702 cells, and primary hepatocytes. The level changes of Cys-SSH in cells stimulated by some related reagents are also observed. The probe is also suitable for deep tissue ratio imaging. Organ targeting tests with Cy-Dise in normal Spraque-Dawley (SD) rats and Walker-256 tumor SD rats verify its predominant localization in the liver. The probe is promising for revealing the roles of Cys-SSH in physiological and pathological processes.